Daisy darker eaudiobook A novel. - Feeney, Alice (Macmillan Audio, 2022)
"Stephanie Racine's talented narration helps create an atmospheric backdrop for this dark mystery."- AudioFile This program is read by longtime narrator Stephanie Racine who has voiced numerous New York Times, U.S. and U.K. bestselling audiobooks. Author Alice Feeney reads the acknowledgments on this program. The New York Times bestselling Queen of Twists returns... with a family reunion that leads to murder. After years of avoiding each other, Daisy Darker's entire family is assembling for Nana's 80th birthday party in Nana's crumbling gothic house on a tiny tidal island. Finally back together one last time, when the tide comes in, they will be cut off from the rest of the world for eight hours. The family arrives, each of them harboring secrets. Then at the stroke of midnight, as a storm rages, Nana is found dead. And an hour later, the next family member follows... Trapped on an island where someone is killing them one by one, the Darkers must reckon with their present mystery as well as their past secrets, before the tide comes in and all is revealed. With a wicked wink to Agatha Christie's And Then There Were None , Daisy Darker' s unforgettable twists will leave listeners reeling. "Wow! Echoes of Christie's And Then There Were None but turned into something wonderfully original and wrapped in a genuinely creepy dysfunctional family fairy-tale of a novel, this takes Feeney to the next level. I LOVED IT!" —Sarah Pinborough, bestselling author of Behind Her Eyes and Insomnia A Macmillan Audio production from Flatiron Books.